Pengaruh Persepsi dan Kualitas Pelayanan terhadap Kepuasan Pasca Pembelian Pengguna Aplikasi Online Shop - Muhammad Anasrullah; Maria Agatha Sri W. H; Farida Nurhana (Fakultas Ekonomi Universitas Panca Marga, 2022)
This study aims to determine the effect of perceptions and service quality on post-purchase satisfaction of online store application users, either simultaneously or partially. This research is a non-experimental quantitative research. The population in this study were students of Bhinneka PGRI University. The sampling technique uses probability sampling method with simple random sampling with a total sample of 92 students. Data collection techniques using a closed questionnaire method. Data analysis techniques used are simple linear regression, multiple linear regression, t test and F test. The results of this study indicate that there is a positive influence of Perception (X1) on Post-Satisfaction Satisfaction (Y) as evidenced from the tcount (10.897)> ttable (1.987) ) with a significance of 0,000 ˂ 0.050 meaning that there is an influence between Perception on Post-Satisfaction Satisfaction. There is a positive influence on Service Quality (X2) on Post-Satisfaction Satisfaction (Y) as evidenced from the value of tcount (9,303)> ttable (1,987) with a significance of 0,000 ˂ 0.050 meaning that there is an influence between Service Quality on Post-Satisfaction Satisfaction. While the results of the F test show the value of Fcount (68.780)> Ftable (3.10) and a significant level of 0.000 ˂ 0.05.